Leiomyoma of the urinary bladder - T Dewaele; L D’Hooghe; St Weyers; P De Visschere (Journal of the Belgian Society of Radiology, 2014)
A routine gynaecological examination in a 26-year-old woman revealed a palpable mass behind the pubic symphysis. Transvaginal ultrasound showed a solid mass of 5 cm between the vagina and the urinary bladder protruding into the bladder. A transvaginal biopsy was performed and the pathological report suggested a benign mesenchymal tumor, most likely a leiomyoma. MRI scan showed a well-circumscribed solid mass on the endovesical side of the right bladder wall. The lesion had a homogenous low signal intensity on T1WI (Fig. A) and a slightly heterogeneous medium signal intensity on T2WI (Fig. B). The lower portion of the lesion extended to the bladder neck (Fig. B, C). On cystoscopy the tumor was covered by intact mucosa and extended close to the right ureteral orifice. Since the patient had initially no complaints ultrasound monitoring was suggested. However, one year later, she developed increased urinary frequency, and it was decided to resect the leiomyoma. Laparotomic resection resulted in a well-circumscribed mass that could relatively easily be removed by enucleation. Laparotomy was preferred over laparascopic resection because of the proximity of the right ureteral orifice. The pathological examination confirmed the diagnosis of a leiomyoma. The postoperative period was uneventful and patient is doing well 15 months after surgery.